HLA class II DRB1 and DQB1 allelic polymorphism and sclerosing lymphocytic lobulitis of the breast. - Lee, A H (1999)
BACKGROUND: Sclerosing lymphocytic lobulitis is an inflammatory disorder of the breast. The pattern of inflammation, expression of HLA class II DR by breast epithelium and association with autoimmune disorders, particularly insulin dependent diabetes mellitus (IDDM), together suggest an autoimmune aetiology. AIM: To test the hypothesis that susceptibility to sclerosing lymphocytic lobulitis may be linked to patient HLA class II DRB1 alleles, particularly DRB1*03 and DRB1*04, suggested by a previous small uncontrolled study. METHODS: HLA class II DRB1 and DQB1 genotypes were compared between a series of 28 sclerosing patients with lymphocytic lobulitis and 300 controls, using polymerase chain reaction (PCR) based typing of DNA extracted from formalin fixed, paraffin embedded biopsies. RESULTS: Results from the 28 patients (nine with IDDM) showed an increased frequency of DRB1*04 compared with controls (61% v 33%, p = 0.01), but no significant differences for other genotypes. In patients with IDDM, the frequencies of DRB1*04 (89%, p = 0.001) and DQB1*0302 (100% v 21%, p = 0.0001)--a genotype that is in linkage disequilibrium with DRB1*04--were increased compared with controls. However, in the patients without IDDM, the frequencies of DRB1*04 (50%) and DQB1*0302 (14%) were not significantly increased. CONCLUSIONS: The increased frequency of HLA DRB1*04 in sclerosing lymphocytic lobulitis appears to reflect its association with IDDM, a condition in which DRB1*04 is increased in frequency.